WAYS TO IMPROVE THE PRACTICE OF USING TOURIST RESOURCES FOR EFFECTIVE DEVELOPMENT OF TOURISM IN THE REGIONS - Abduvakhidova Nargiza Akbarjonovna, Akbarjonovna (THE INNOVATION ECONOMY, 2025)
This article studies the current state, problems and prospects of using existing tourist resources in various regions of Uzbekistan. The possibilities of developing regional tourism through full use of tourist potential, development of infrastructure, improvement of marketing and management systems are highlighted. Also, practical recommendations are developed based on advanced foreign experience. The article may be useful for specialists, entrepreneurs and researchers who shape tourism policy.